Genotype-phenotype correlations in patients with de novo KCNQ2 pathogenic variants. (December 2020) - Malerba, Federica; Alberini, Giulio; Balagura, Ganna; Marchese, Francesca; Amadori, Elisabetta; Riva, Antonella; Vari, Maria Stella; Gennaro, Elena; Madia, Francesca; Salpietro, Vincenzo; Angriman, Marco; Giordano, Lucio; et al.
Abstract : Objective: Early identification of de novo KCNQ2 variants in patients with epilepsy raises prognostic issues toward optimal management. We analyzed the clinical and genetic information from a cohort of patients with de novo KCNQ2 pathogenic variants to dissect genotype-phenotype correlations. Methods: Patients with de novo KCNQ2 pathogenic variants were identified from Italy, Denmark, and Belgium. Atomic resolution Kv7.2 structures were also generated using homology modeling to map the variants. Results: We included 34 patients with a mean age of 4.7 years. Median seizure onset was 2 days, mainly with focal seizures with autonomic signs. Twenty-two patients (65%) were seizure free at the mean age of 1.2 years. More than half of the patients (17/32) displayed severe/profound intellectual disability; however, 4 (13%) of them had a normal cognitive outcome. A total of 28 de novo pathogenic variants were identified, most missense (25/28), and clustered in conserved regions of the protein; 6 variants recurred, and 7 were novel. We did not identify a relationship between variant position and seizure offset or cognitive outcome in patients harboring missense variants. Besides, recurrent variants were associated with overlapping epilepsy features but also variable evolution regarding the intellectual outcome. Conclusions: We highlight the complexity of variant interpretation to assess the impact of a class of de novo KCNQ2 mutations. Genetic modifiers could be implicated, but the study paradigms to successfully address the impact of each single mutation need to be developed.